Electrophysiologic Conservation of Epicardial Conduction Dynamics After Myocardial Infarction and Natural Heart Regeneration in Newborn Piglets - Wang, Hanjay; Pong, Terrence; Obafemi, Oluwatomisin O.; Lucian, Haley J.; Aparicio-Valenzuela, Joy; Tran, Nicholas A.; Mullis, Danielle M.; Elde, Stefan; Tada, Yuko; Baker, Sam W.; Wang, Caroline Y.; Cyr, Kevin J.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Newborn mammals, including piglets, exhibit natural heart regeneration after myocardial infarction (MI) on postnatal day 1 (P1), but this ability is lost by postnatal day 7 (P7). The electrophysiologic properties of this naturally regenerated myocardium have not been examined. We hypothesized that epicardial conduction is preserved after P1 MI in piglets. Yorkshire-Landrace piglets underwent left anterior descending coronary artery ligation at age P1 (n=6) or P7 (n=7), After 7 weeks, cardiac magnetic resonance imaging was performed with late gadolinium enhancement for analysis of fibrosis. Epicardial conduction mapping was performed using custom 3D-printed high-resolution mapping arrays. Age- and weight-matched healthy pigs served as controls (n=6). At the study endpoint, left ventricular (LV) ejection fraction was similar for controls and P1 pigs (46.4±3.0% vs 40.3±4.9%, p=0.132), but significantly depressed for P7 pigs (30.2±6.6%, p<0.001 vs control). The percentage of LV myocardial volume consisting of fibrotic scar was 1.0±0.4% in controls, 9.9±4.4% in P1 pigs (p=0.002 vs control), and 17.3±4.6% in P7 pigs (p<0.001 vs control, p=0.007 vs P1). Isochrone activation maps and apex activation time were similar between controls and P1 pigs (9.4±1.6 vs 7.8±0.9 ms, p=0.649), but significantly prolonged in P7 pigs (21.3±5.1 ms, p<0.001 vs control, p<0.001 vs P1). Conduction velocity was similar between controls and P1 pigs (1.0±0.2 vs 1.1±0.4 mm/ms, p=0.852), but slower in P7 pigs (0.7±0.2 mm/ms, p=0.129 vs control, p=0.052 vs P1). Overall, our data suggest that epicardial conduction dynamics are conserved in the setting of natural heart regeneration in piglets after P1 MI.